A Review of Minimally Invasive Techniques for Perfusion Optimization of Flaps - Tobin, Micaela; Thomas, Charlotte; Raquepo, Tricia; Yamin, Mohammed; Mustoe, Audrey; Posso, Agustin; Foppiani, Jose; Cauley, Ryan P. (Journal of Reconstructive Microsurgery, 2025)
There is a growing emphasis on minimally invasive techniques as an alternative to surgical delay to promote vessel reorganization and prevent partial and total flap loss. This systematic review evaluates existing literature on these minimally invasive techniques, focusing on their potential applications in preventing ischemia-related complications.A systematic review was conducted in July 2024 using PubMed, MEDLINE, and Web of Science following preferred reporting items for systematic reviews and meta-analysis guidelines. Inclusion criteria were studies that included patients undergoing any flap-based reconstruction treated with minimally invasive delay. Exclusion criteria were non-English papers, other systematic reviews, nonhuman patients, and pediatric patients.Six studies were included (angiographic delay n = 143, heat preconditioning n = 191, ischemic preconditioning n = 60) which examined minimally invasive methods for perfusion optimization. Aggregated data from the three studies on angiographic delay demonstrated a 13% (18/143) combined skin or fat flap necrosis rate, which was lower than that of non-delayed flaps and comparable to more invasive traditional surgical ligation. Ischemic preconditioning showed no significant differences (p = 1.0) g compared with controls, whereas heat preconditioning led to reductions (26% vs. 35%) in flap necrosis and necrosis requiring surgical intervention (11% vs. 17%).Angiographic embolization presents a promising alternative to invasive surgical delay, effectively reducing flap necrosis risk. Heat and ischemic preconditioning also show potential for increasing flap survival, although current studies are limited by small sample sizes. Further research is essential to explore preoperative conditioning interventions to improve surgical outcomes for patients who require less invasive delay techniques.
Keywords: perfusion; heat preconditioning; ischemic preconditioning; angiographic embolization; preoperative conditioning